Eggshell Powder as an Adsorbent for Removal of Lead (II) in Panchor’s River - Mohamad Mahani , Norul Ahsanah Aulia; Hamidon, Nuramidah (Journal of Advanced Industrial Technology and Application, 2021)
Heavy metal such as lead has increase in the natural environment especially in the aqueous solution. Remediation method of adsorption offer a treatment for removing heavy metal in river. This experiment is to analyse and compare eggshell adsorbent of activated carbon in Panchor’s river through its efficiency in removing heavy metal of Lead (II). Eggshell is designed as an activated carbon through physical and chemical activation in treating the water by undergoing adsorption process of few laboratory test. The efficiency of eggshell chemical activated carbon is high as the percentages removal of Pb is 48.21% compare to physical activated carbon with 32.14%. However, this study showed that both eggshell activated carbon is an effective adsorbent in removing Pb from aqueous solution of natural environment